RE-DESIGN BANGUNAN DAN IMPLEMENTASI KONSEP “BIOPHILIC DESIGN” UNTUK MENINGKATKAN KUALITAS RUANG PADA GEREJA GPPS DI SURABAYA - Felicia Wisama Nugraha; Indah Nuraini Fahroni; Febriani Elisabeth Openg (Narada : Jurnal Desain dan Seni, 2019)
Gereja Pantekosta Pusat Surabaya (GPPS) is a Christian Church that was established since February 25, 1964, with the spirit of devotion to give service for God. In the beginning, GPPS Church has more or less 50 permanent congregations and keep growing until now reaches the number around 120 congregations. Because of the layout and the size of this Church building is small, it makes the congregations feel uncomfortable and even have to worship on the outside of the Church. Furthermore, this situation disturbs the sacredness in worship for a few congregations. Moreover, the inadequate implementation of these interior design styles also interferes with the humility of the worship and reduces the quality of every room. Therefore, it is needed for this Church to re-design the layout of the building and the implementation of the biophilic concept to support the humility and increase the quality of the rooms in the GPPS Church Surabaya. This design uses the Design Thinking methodology which consists of Observe, Point of View, Ideate, Prototype, and Test and implements the Biophilic Design with the concept “ Heaven of the Earth “ which aims to take benefit of the surrounding nature. This concept is expected to increase the atmosphere of Interior Design to have better humility and give more place for other congregations.